Cosmopolitan Education in the Islamic perspective - Arbaiyah Yusuf; Mukhoiyaroh Mukhoiyaroh; Muh. Tajab (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
This research is an examination of “Cosmopolitan Education in the Islamic perspective The principle aspects which are wanted to be known are: (1) The meaning of Cosmopolitan education in the Islamic perspective. (2) The Basis of Cosmopolitan education in Islam. (3) How does the concept of Cosmopolitan education gives implications for human life? (4) The Contribution of Cosmopolitan education toward human life in the revolution era 4.0 as the digital era. The research shows that education in the Islamic perspective goes from the time when Allah blows the ruh to the body until the last opportunity to taking an effort. Cosmopolitan education gives an important implication in which humans as individuals and humans as a society can become a perfect men. According to Islam, Muttaqi is the highest perfection which has many aspects of goodness. Cosmopolitan education gives a meaningful contribution to the life of human beings in the revolution era 4.0 as the digital era.